Precarious Lives of Rohingya Refugee Women Emerging as Caregivers: A Visual Analysis of the Refugee Webcomic I Am a Leader of My House - Bali, Rishav; Malhotra, Isha (SARE: Southeast Asian Review of English, 2024)
The paper offers a close analysis of the refugee webcomic titled I am a Leader of My House, produced online in 2021 by the non-profit organization PositiveNegatives in partnership with The New Humanitarian, to decipher the everyday struggle of Rohingya refugee women through the interaction of the two female protagonists, Romida and Hafsa whose roles as agentic survivors tend to transform the lives of other refugee women in the Cox’s Bazaar refugee camp in Bangladesh. Drawing on Judith Butler’s concepts of “precarity” and “frames of recognition” the paper textually and visually examines the individual challenges they face, as women emerging in leadership roles against the cultural and neoliberal norms, to “care” for the vulnerable women and children in the camps. The gendered dimension adds another layer to the form of life already burdened with a precarious legal status as women’s reproductive health, maternal care, and the specific challenges they face are often overlooked. The paper argues for recognizing such challenges and assigning them more responsibilities which can be a strategic and empathetic response to address their specific needs while it is also a culturally sensitive approach considering the conservative cultural norms and restricted interactions between genders in the Rohingya society.